Ulnar collateral ligament repair in professional baseball players - Ajith Malige; Carlos Uquillas (Clinics in Shoulder and Elbow)
Background While initial reports of surgical repair are promising, literature detailing post-repair outcomes is lacking. This study explores the effectiveness of ulnar collateral ligament (UCL) repair in returning professional baseball players to their pre-injury level of play. Professional baseball players undergoing UCL repair will have successful outcomes and high return to sport rates after surgery. Methods From 2016 to 2021, publicly available databases were utilized to search for professional baseball players who underwent UCL repair. Players were included if they underwent primary UCL repair with an internal brace. Players were excluded if they underwent revision UCL repair, UCL reconstruction, or were amateur baseball players. Results Of the 11 pitchers that underwent UCL repair, MiLB pitchers returned to sport at an average of 17.5 months. MiLB pitchers had similar ERA, games played, innings pitched, and walks plus hits per inning pitched (WHIP) before and after surgery. Four MLB pitchers (80%) returned to sport at 9.55 months. MLB pitchers had fewer games played and innings pitched but similar ERA and WHIP in after versus before surgery. Pitch velocity and spin rates after surgery varied based on pitch type. The 7 positional players who underwent UCL repair showed no differences in batting or fielding performances before versus after surgery. Conclusions UCL repair can successfully return both pitchers and positional players at both the MiLB and MLB level back to play at pre-injury levels. Repair can be considered as an option in the right type of injury for players hoping to maximize performance after surgery with minimal recovery time. Level of evidence IV.